Etymological and social context of the term physical culture and sport - Arkadiusz Kaźmierczak (Kazimierz Wielki University, 2019)
The basis for isolating the concept of physical culture and the educational role of sport from the field of contemporary culture is a number of factors that are a consequence of socio-cultural, civilizational-technical and economic changes. The relationship between culture, physical culture and sport has been and will probably continue to be the subject of scientific considerations of many representatives of social sciences, humanities and, above all, physical culture sciences. Nowadays, it seems that the majority of experts on the subject advocate the recognition of physical culture and sport as elements of an autotelic social system, which, together with other fields of culture, promote education of the value of the body as a paradigm necessary for human development. The objective nature of physical culture and sport in achieving general goals refers to such values as: health, lifestyle, education for an active life, care for a beautiful and fit body, a high level of physical fitness.